EFEKTIFITAS PENGAJARAN METODE EKSPERIMEN TAK TERINTEGRASI DIDAHULUI PEMBERIAN PETA KONSEP TERHADAP PRESTASI BELAJAR SISWA KELAS II SEMESTER III SMU BATIK 2 SURAKARTA - ARINI, ARYANTI; OETOMO, DWI; HARLITA, HARLITA (Bioedukasi: Jurnal Pendidikan Biologi, 2004)
The purpose of this research is to compare the un-integrated experimental and lecture teaching methods. In the un-integrated experimental teaching method, the students are given a concept chart first. The subject matter of this research is the movement on plants.This research used experimental method with randomized control-group only design. The populations are the second grade students of SMU Batik 2 Surakarta, year 2002/2003. The sample is 86 students that taken using cluster random sampling technique. The first data are taken from the value of once grade students of a quarter monthly III. They are used to test the early ability of students. The second data are gotten from post test. Data are analyzed using t-test.The conclusion of this research is that the teaching using un-integrated experimental methods is more effective to increase the achievement of students than lecture method.